Identifying plant species using architectural features in leaf microscopy images - Florindo, Joao Batista; Bruno, Odemir Martinez; Rossatto, Davi Rodrigo [UNESP]; Kolb, Rosana Marta [UNESP]; Gómez, Maria Cecilia; Landini, Gabriel (Canadian Science Publishing, 2016)
This work proposes an analytical method to identify plant species based on microscopy images of the midrib cross-section of leaves. Unlike previous shape-based approaches based on the individual shape of external contours and cells, an architectural analysis is proposed, where the midrib is semi-automatically segmented and partitioned into histologically relevant structures composed of layers of cells and vascular structures. Using a sequence of morphological operations, a set of geometrical measures from the cells in each layer is extracted to produce a vector of features for species categorization. The method applied to a database containing 10 species of plants from the Brazilian flora achieved a success rate of 91.7%, outperforming other classical shape-based approaches published in the literature.
Keywords: Automatic species identification; Image analysis; Morphological features